Metode Kitab Syarah Dalam Menetapkan Makna Hadis Berpandukan Dalil: Suatu Penelitian Awal: The Method of Syarah Book in Determining the Meaning of Hadith Based on Evidence: A Preliminary Analysis - Ahmad Izzuddin Abu Bakar (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
Syarah book or commentaries was embraced not only in the exposition of individual hadith of the Prophets SAW and hadith collections, but also in other sub disciplines such as the science of hadith transmission. The debate is so subtle and deep that it covers various types of knowledge. Therefore, there are difficulties in reviewing and filtering opinions on the meaning of hadith based on evidence (dalil). This article aims to identify and highlight the methods used by these books in establishing a meaning or description that coincides with the correct evidence and argumentations (pendalilan) or vice versa. The methodology used is the Library Method where relevant documents are collected and their contents are analyzed. A review of the practice of syarah books was conducted on selected sections of the following books; Fatḥ al-Bārī Šarḥ Ṣaḥīḥ al-Buḫārī, Iršād al-Sārī Šarḥ Ṣaḥīḥ al-Buḫārī, al-Mufhim Limā Uškila Min Talḫīs Saḥīḥ Muslim son of al-Tauḍīḥ Lišarḥ al-Jāmi ’al-Saḥīḥ. At least five (5) methods have been identified. First: List the Opinions and its Evidence (dalil), second: Discuss the Argumentations Used, third: State a View as Accurate (Rājiḥ), fourth: State the View is Not Based on Evidence or Argumentations That Are Not Strong and fifth: Indicate the Existence of Objection to a View. The findings of this study will ease the extraction of the meaning of the hadith that are aligned with the evidence of the syara’ (Islamic law).